Instruments to measure nursing competencies: systematic review - Vallejo-Gómez, Lucero (Universidad de Sonora, 2021)
Introduction: It is of special interest to evaluate professional competencies in higher education and to have valid and reliable instruments or scales in nursing that identify existing competencies and those that are acquired during the process from student to professional. Objective: To identify the instruments with validity and reliability that exist to measure comprehensive competencies in nursing students and professionals. Methodology: A systematic review was carried out in the databases PubMed, Scielo, Redalyc and with snowball method; articles published between 2000 and 2020 in English, Spanish and Portuguese were analyzed; the terms "competencies in nursing", "measurement instruments", "construction and validation", "competency measurement scales" and "validity and reliability" were used according to the descriptors DeCS, and MeSH.  Results: 15 articles met the inclusion criteria. It was reported that 66% were original instruments; the mean number of items was 41.5; 80% were published in English; 33% in Asian countries, 20% in Nordic countries and 20% in Brazil; all reported reliability and validity to assess psychometric properties; 26% used Patricia Benner's theory as a theoretical reference; the study population were students, professionals and nursing specialists; different nursing subjects and specialties were used to assess competencies. Conclusions: Measurement instruments for nursing competencies are designed and adapted cross-culturally, although there is no uniformity in the application of statistical tests.